2018
DOI: 10.1007/s10531-018-1584-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enhancement of biodiversity occurrence records using unconventional specimen data

Abstract: Distributions of taxa across time and space are central to understanding biodiversity and biotic change, yet currently available occurrence data, drawn from biodiversity specimen records and observational datasets, are often insufficient to answer many driving questions. Records of "associated taxa," taxa co-occurring with a specimen at the time and place of collection, have the potential to fill data gaps and expand the spatiotemporal scope of current occurrence records. I developed a method to extract associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Specimens of different species that were collected together could be compared or considered in analyses. Similarly, "associated species" are frequently provided by collectors on specimen labels (Landrum and Lafferty 2015;Pearson 2018). These metadata are mostly unused.…”
Section: Addressing Effects Of Microsite Variationmentioning
confidence: 99%
“…Specimens of different species that were collected together could be compared or considered in analyses. Similarly, "associated species" are frequently provided by collectors on specimen labels (Landrum and Lafferty 2015;Pearson 2018). These metadata are mostly unused.…”
Section: Addressing Effects Of Microsite Variationmentioning
confidence: 99%
“…In examining sampling bias in Australia, New England (U.S.A.), and South Africa from ~5 million digitized herbarium records, Daru et al (2018) found that graminoid specimens in Australia and South Africa were overrepresented compared to New England, which overrepresented herbs and trees. In examining co-associated taxa compared to specimen data for the Robert K. Godfrey Herbarium (FSU), Pearson (2018) found that fewer graminoids were included as associated taxa records (20.9%) compared to specimen records (26.8%), showing that graminoids are underrepresented as co-associated taxa. In comparison to arctic herbarium collection bias in Nunavut, Canada, eastern Arkansas also exhibits under-collection of Asteraceae, Fabaceae, and Ranunculaceae (Panchen et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…We prefer the ‘ResourceRelationship’ field but agree with Downey (1998) that a field for ‘host plant’ in databases and specimen labels would eliminate confusion with species that are only associated. An extension to the Darwin Core controlled vocabulary framework for parasitic plants with standardized terms for these important interrelationships would provide a more information‐rich description of their ecologies and greater accuracy for web‐based applications and data analysis protocols (Myltsev & Mozzherin, 2016; Pearson, 2018) that extract taxon information from digitized records. It is crucial, however, that both the original voucher label and the digitized specimen host taxa are annotated similarly, as to avoid confusion.…”
Section: Best Practices For Collecting Preparing and Curating Parasit...mentioning
confidence: 99%